Effect of advanced glycation end products on platelet activation and aggregation: a comparative study of the role of glyoxal and methylglyoxal. (19th May 2021) - Arriagada-Petersen, Cristian; Fernandez, Paula; Gomez, Maira; Ravello, Natalia; Palomo, Iván; Fuentes, Eduardo; Ávila, Felipe
Abstract: Advanced glycation end products (AGEs) arising from dietary intake have been associated with numerous chronic diseases including cardiovascular diseases. The interaction between platelets and AGEs has been proposed to play a role in the etiology of cardiovascular diseases. However, the effects of the interaction between platelets and Maillard reaction products generated from glyoxal (Gly) or methylglyoxal (MG) are poorly understood. In this work, the effects of AGEs generated by the reaction between Gly or MG with Lys or bovine serum albumin (BSA) on platelet activation and aggregation were assessed. AGEs were generated incubating Gly or MG with Lys or BSA during 5 hours or 14 days, respectively. AGEs generation were characterized by kinetic studies and by amino acid analysis. Human platelet-rich plasma (PRP) was incubated with different concentrations of AGEs from Lys-MG or Lys-Gly and BSA-MG or BSA-Gly. Platelet activation was determined quantifying the expression of CD62 ( P -selectin) in PRP exposed to different AGEs concentrations. It was found that Lys-MG and Lys-Gly induced an increase in P -selectin expression ( p < .05), being 33.9% higher for Lys-MG when compared to Lys-Gly. Platelets incubated in the presence of BSA-MG and BSA-Gly did not show an increase in the P -selectin expression. Platelet aggregation was significantly higher for the mixture Lys-MG (in all the range of concentrations evaluated), whereas for Lys-Gly it was only significant the highest concentration (Lys 168 µM/Gly 168 µM). It was observed a significant increase in platelet aggregation induced by ADP for samples BSA-Gly. AGEs formed with MG-Lys induce a higher activation and aggregation of platelets when compared to those formed from Gly-Lys.